INDONESIA-NORWAY COOPERATION TO REDUCE GREENHOUSE GAS EMISSIONS THROUGH REDD + SCHEMES (CASE STUDY: FORESTS OF CENTRAL KALIMANTAN) - Christin Sicilia Blandina Ansanay (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2018)
Environmental problems, in particular, climate change is of international concern as this issue is directly related to human life using natural resources such as forests, regardless of environmental carrying capacity and ecosystem sustainability. It will undoubtedly affect the economy because natural resources have economic and social functions that provide benefits and become the foundation for the sustainability of the lives of nations in the world, especially in reducing the impact of climate change. The purpose of this research is to know the cooperation between Indonesia dan Norway to reduce greenhouse gas emission (GHG) through Reducing Emissions from Deforestation and Forest Degradation (REDD+) scheme. The benefits of the research are theoretically useful for the development of the International Relations of science, especially concerning the cooperation of the environment. The theory used as the basis of the author in answering the question is the theory of constructivism. The method used in this study is descriptive qualitative. The results of this research indicate that the cooperation between Indonesia and Norway runs well through the preparation and transition phase, but not yet at the full implementation stage so that there has been no result of reduction of gas emissions a significant deforestation and degradation. However, this cooperation has a positive impact on improving forest governance for Indonesia and raising awareness government and communities to safeguard and conserve forests to reduce carbon emissions through the formation of policies in Indonesia.